Advanced Practice Professionals and an Outpatient Clinic: Improving Longitudinal Care in an Interventional Radiology Practice - Crum, Elizabeth A.; Varma, Manish K. (Seminars in Interventional Radiology, 2019)
The field of interventional radiology (IR) has made tremendous advances in both scope and practice since its inception in the early 1960s. With these advances, it has solidified itself as a valuable subspecialty to the medical community and, most importantly, to the patients who receive IR care. Expanding clinical services to improve care in both the pre- and postprocedural setting is a logical step in IR maturation. The use of advanced practice professionals, in the form of physician assistants and nurse practitioners, can add value in both quality of the patient experience and exposure to other subspecialties. Furthermore, a dedicated outpatient clinic provides a centralized site to evaluate patients and communicate with referring services. These additions can be a challenging value proposition, particularly when working in a combined diagnostic radiology and IR practice, but given the benefits, these are well worth the time and monetary investments.
Keywords: interventional radiology; advanced practice professionals; outpatient clinic; interventional radiology/diagnostic radiology; physician assistants; nurse practitioners